A behavioral analysis of online loan application adoption: The roles of ease of use, risk, and trust in Rural Bali - Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Santikasari, Ni Nengah (Universitas Negeri Yogyakarta, 2024)
The rapid advancement of technology, particularly in digital financial services, has significantly facilitated various societal activities, wherein individual behaviors to adopt new technologies are crucial factors. This study analyses the influence of perceived ease of use, perceived risk, and trust on the intention to use online loan applications among residents of Bangli, a rural regency in Bali, who have not yet adopted such applications. Utilizing an explanatory research design and a quantitative approach, this study involved 96 respondents selected through a nonprobability sampling method with a purposive sampling technique. Several analytical methods were employed, including validity and reliability testing, classical assumption testing, and multiple linear regression analysis. The findings reveal that perceived ease of use, perceived risk, and trust significantly affect adoption intentions both partially and simultaneously, with ease of use and trust positively influencing these intentions, while perceived risk has a negative effect on adoption intentions. This study contributes to international marketing management by offering insights into user behavior and the elements that foster or hinder fintech adoption in rural settings. By focusing on the roles of ease of use, risk perception, and trust, it provides a renewed perspective for enhancing the global expansion of fintech services.Keywords: Perceived Ease of Use; Perceived Risk; Trust; Intention to Use; Online Loan Application Adoption